Tissue response and clinical outcomes after cardiovascular use of porcine small intestinal small intestinal submucosal extracellular matrix: a systematic review - Villads Juul Bruun; Line Lyngbak Jensen; J. Michael Hasenkam; J. Michael Hasenkam; Johannes H. Jedrzejczyk; Johannes H. Jedrzejczyk (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPorcine small intestinal submucosal extracellular matrix (PSIS-ECM) is a biomaterial that has gained increasing popularity in cardiovascular surgery over the past three decades. This popularity is due to PSIS-ECM demonstrating properties of an ideal biological scaffold; it is easy to use, lacks immunogenicity, is absorbable, possesses the potential to promote native tissue growth, and exhibits remodelling properties. We systematically reviewed the literature on the preclinical and clinical use of this approach in cardiovascular surgery over the past decade.MethodsUtilizing a box-search methodology, an extensive survey of the literature on PSIS-ECM's application in cardiovascular surgery from 2013 until September 2023 was conducted within the PubMed and Embase databases. Initially, 245 publications were identified. Following title, abstract, and full-text screening, 66 articles were included in the survey.ResultsAmong nine preclinical studies conducting histological assessments of explants, eight did not report signs of inflammation. Tissue remodelling was documented in six preclinical studies. Histological examination of explants was incorporated into thirteen clinical cohort studies, all of which demonstrated varying intensities of inflammation and no or minimal signs of regeneration and remodeling. The reintervention rates among clinical cohort studies range from 4.5% to 87.5%. Eleven studies reported a reintervention rate exceeding 15%, while six reported a reintervention rate below 15%.ConclusionPreclinical studies corroborate the notion that PSIS-ECM exhibits properties of an ideal biological scaffold. However, these findings lack reproducibility in clinical settings. Combined with reports from clinical studies showing reintervention rates exceeding 15%, this has raised concerns about whether clinical application of PSIS-ECM should be confined to selected cases.